Chronotropics Caribbean Women Writing Spacetime - Ferly, Odile; Zimmerman, Tegan (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book deconstructs androcentric approaches to spacetime inherited from western modernity through its theoretical frame of the chronotropics. It sheds light on the literary acts of archival disruption, radical remapping, and epistemic marronnage by twenty-first-century Caribbean women writers to restore a connection to spacetime, expanding it within and beyond the region. Arguing that the chronotropics points to a vocation for social justice and collective healing, this pan-Caribbean volume returns to autochthonous ontologies and epistemologies to propose a poetics and politics of the chronotropics that is anticolonial, gender inclusive, pluralistic, and non-anthropocentric.